2015
DOI: 10.1088/0029-5515/55/12/123005
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on FTU dust and on the origin of ferromagnetic and lithiated grains

Abstract: A comprehensive analysis of composition and morphology of metallic micrometric particles collected in FTU during the 2013 shut-down is presented. The data-set analyzed is the result of years of experimental activity in FTU which is a full metal machine since the beginning of operation and with a liquid lithium limiter (LLL) from 2005. It was found that the metallic population, consisting of flakes, smashed and spheroidally shaped particles from plasma facing components (mainly SS and Mo), exhibits an unexpecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…It has been suggested that ferromagnetic dust can be generated in tokamaks by a non-equilibrium austenite-to-ferrite phase transformation that is induced by rapid temperature quenching in the presence of strong external magnetic fields [8]. Moreover, there is strong experimental evidence of pre-plasma remobilization of ferromagnetic dust in FTU that has been further supported by theoretical estimates [16].…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…It has been suggested that ferromagnetic dust can be generated in tokamaks by a non-equilibrium austenite-to-ferrite phase transformation that is induced by rapid temperature quenching in the presence of strong external magnetic fields [8]. Moreover, there is strong experimental evidence of pre-plasma remobilization of ferromagnetic dust in FTU that has been further supported by theoretical estimates [16].…”
Section: Introductionmentioning
confidence: 87%
“…(a) FTU. The dust was collected by gross vacuuming around the vessel floor and was meshed out into two different size groups [8]. The batch with sizes m was considered in the present investigation.…”
Section: Magnetic Dust Collection and Vessel Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…cryogenic walls of FTU. The presence of ferromagnetic particles in tokamaks could pose new problems due to their interaction with the magnetic field; in fact magnetic grains could be liftedup during the ramping-up phase of the magnetic field due to ∇B force, and interfere with the start-up phase of plasma pulse [28].…”
Section: Liquid Lithium Limiter (Lll)mentioning
confidence: 99%